Ron White : [videorecording (DVD)] they call me "Tater Salad" - White, Ron, 1956-; White, Ron, 1956- (Parallel Entertainment ; Distributed by Image Entertainment, 2004)
One of the stars of the hit film Blue Collar Comedy Tour, The Movie, Ron White is the razor-sharp Texan who earned his reputation with his acerbic wit performing stand-up across the United States for the past 18 years.